Single subject controlled experiments in aphasia: The science and the state of the science - Thompson, Cynthia K. (Journal of communication disorders, 2006)
This paper discusses the use of single subject controlled experimental designs for investigating the effects of treatment for aphasia. A brief historical perspective is presented, followed by discussions of the advantages and disadvantages of single subject and group approaches, the basic requirements of single subject experimental research, and crucial considerations in design selection. In the final sections, results of reviews of published single subject controlled experiments are discussed, with emphasis on internal validity issues, the number of participants enrolled in published studies, operational specification of the dependent and independent variables, and reliability of measurement. Learning outcomes: As a result of reading this paper, the participant will: (1) understand the mechanisms required for demonstration of internal and external validity using single subject controlled experimental designs, (2) become familiar with the basic requirements of single subject controlled experimental research, (3) understand the types of single subject controlled experimental designs that are the most appropriate for studying the effects of treatment for aphasia, and (4) become familiar with trends in the published aphasia treatment literature in which single subject controlled experimental designs have been used.